2008
DOI: 10.1007/s11606-008-0756-0
|View full text |Cite
|
Sign up to set email alerts
|

Fear, Fatalism and Breast Cancer Screening in Low-Income African-American Women: The Role of Clinicians and the Health Care System

Abstract: BACKGROUND: African-American women have the highest breast cancer death rates of all racial/ethnic groups in the US. Reasons for these disparities are multi-factorial, but include lower mammogram utilization among this population. Cultural attitudes and beliefs, such as fear and fatalism, have not been fully explored as potential barriers to mammography among African-American women. OBJECTIVE:To explore the reasons for fear associated with breast cancer screening among low-income African-American women. METHOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
116
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(126 citation statements)
references
References 24 publications
9
116
0
1
Order By: Relevance
“…The authors support previous researchers by pointing out the fact that research on the construct of cancer fatalism among persons diagnosed with cancer is sparse, as much of the research on this topic has focused on noncancer participants and the influence of cancer fatalism on screening behaviors [1][2][3][4][5][6][7][8][9][10]. Findings from this study raise the question of whether the philosophical underpinnings of fatalism, as it relates to screening, change or are perhaps different once an individual becomes a survivor.…”
supporting
confidence: 54%
“…The authors support previous researchers by pointing out the fact that research on the construct of cancer fatalism among persons diagnosed with cancer is sparse, as much of the research on this topic has focused on noncancer participants and the influence of cancer fatalism on screening behaviors [1][2][3][4][5][6][7][8][9][10]. Findings from this study raise the question of whether the philosophical underpinnings of fatalism, as it relates to screening, change or are perhaps different once an individual becomes a survivor.…”
supporting
confidence: 54%
“…Perhaps this could be due to the fear of females from being diagnosed with breast cancer, which was also one of the common barriers in the current study. On the other hand, physicians and the health system play an important role in creating and perpetuating fear in females about breast cancer screening methods, where poor communication between the patient and healthcare providers is responsible for high degrees of fear among females (33). One limitation of this study was that all the data was collected through self-reports and may be prone to recall bias.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that compared with women of different backgrounds, African American females displayed a generalized fear of the health care system and a sense of fatalism (fear of imminent death upon diagnosis of breast cancer). 21 These factors may contribute to the fact that African American women present with breast cancer at later stages of the disease. 3 …”
Section: Fear Of Breast Cancer Screeningmentioning
confidence: 99%